Preparation and property studies of new detectors of transuranium elements - Andryushchenko, A.Yu.; Blank, A.B.; Budakovsky, S.V.; Zelenska, O.V.; Shevtsov, M.I. (Functional Materials, 2006)
The possibility to use porous scintillators based on the organic molecular crystal of p-terphenyl for determination of a-nuclides in the environmental water has been shown. The technological methods of the porous scintillator preparation have been improved. As a selective sorbent for transuranium elements, the strong-basic anion-exchange resin VP- lAp was used. The operation efficiency of the prepared material has been checked using model systems of ²³⁹Pu reference solutions.